Syntactic Prediction Adaptation Accounts for Language Processing and Language Learning. Issue 4 (13th July 2021) - Havron, Naomi; Babineau, Mireille; Fiévet, Anne‐Caroline; de Carvalho, Alex; Christophe, Anne
Abstract: A previous study has shown that children use recent input to adapt their syntactic predictions and use these adapted predictions to infer the meaning of novel words. In the current study, we investigated whether children could use this mechanism to disambiguate words whose interpretation as a noun or a verb is ambiguous. We tested 2‐ to 4‐year‐old French children using the phrase la petite followed by a homophone that could be interpreted as either a noun or a verb. We assigned the children to a noun condition or a verb condition. Before the test, those in the noun condition were exposed to sentences where la petite predicted nouns, and those in the verb condition to sentences where la petite predicted verbs. At testing, 3‐ to 4‐year‐olds, but not 2‐year‐olds, from the verb condition looked at the verb interpretation longer than did the children in the noun condition. This suggests a progression in children's ability to rely on input to adapt their predictions in language comprehension. Abstract :